Does interspecies hybridization affect the host specificity of parasites in cyprinid fish? - Simková, Andrea; Dávidová, Martina; Papoušek, Ivo; Vetešník, Lukáš (Parasites & vectors, 2013)
BACKGROUND: Host specificity varies among parasite species. Some parasites are strictly host-specific, others show a specificity for congeneric or non-congeneric phylogenetically related host species, whilst some others are non-specific (generalists). Two cyprinids, Cyprinus carpio and Carassius gibelio, plus their respective hybrids were investigated for metazoan parasites. The aim of this study was to analyze whether interspecies hybridization affects host specificity. The different degrees of host specificity within a phylogenetic framework were taken into consideration (i.e. strict specialist, intermediate specialist, and intermediate generalist). METHODS: Fish were collected during harvesting the pond and identified using meristic traits and molecular markers. Metazoan parasite species were collected. Host specificity of parasites was determined using the following classification: strict specialist, intermediate specialist, intermediate generalist and generalist. Parasite species richness was compared between parental species and their hybrids. The effect of host species on abundance of parasites differing in host specificity was tested. RESULTS: Hybrids harbored more different parasite species but their total parasite abundance was lower in comparison with parental species. Interspecies hybridization affected the host specificity of ecto- and endoparasites. Parasite species exhibiting different degrees of host specificity for C. carpio and C. gibelio were also present in hybrids. The abundance of strict specialists of C. carpio was significantly higher in parental species than in hybrids. Intermediate generalists parasitizing C. carpio and C. gibelio as two phylogenetically closely related host species preferentially infected C. gibelio when compared to C. carpio, based on prevalence and maximum intensity of infection. Hybrids were less infected by intermediate generalists when compared to C. gibelio. CONCLUSIONS: This finding does not support strict co-adaptation between host and parasite genotypes resulting in narrow host specificity, and showed that hybrid genotypes are susceptible to parasites exhibiting host specificity. The immune mechanisms specific to parental species might represent potential mechanisms explaining the low abundance of parasites in C. gibelio x C. carpio hybrids.
Keywords: Cyprinidae; Gene Transfer, Horizontal; genotyp; hostitelská specificita; Animals; paraziti; Parasites; přenos genů horizontální; Genotype; Host Specificity; zvířata